(untitled) (Journal of the College of Basic Education, 2022)
The aim of the current research is as follows: - Recognize the expectations of the sexual role of special education teachers Knowing the personality type (A-B) of special education teachers Knowing the statistically significant differences in the expectations of the sexual role according to the gender variable (male-female) Knowing the statistically significant differences in personality type (A - B) according to personality type (male - female). Knowing the relationship between sexual role expectations and A-B personality type among special education teachers The current research community is defined by the teachers of the special education community in primary schools affiliated with the directorates of education (Al-Rusafa and Al-Karkh) for the academic year (2021-2022), and the number of members of the research sample consisted of (150) teachers and commentators from the research community, which were chosen randomly. Male and (80) female researchers. High expectations of the sexual role of the research sample . Sample of special education teachers of personality type B . Meals are no different from females in their expectations about the sexual role . There are significant differences in personality type B and in favor of meals . High correlation between expectations of sexual role and personality type B in the sexual relations diagram A (0.12) Personality B.